A inexpressão na obra Água Viva de Clarice Lispector - Corrêa, Janaina Alves Brasil (2006)
This study aims at analyzing a literary work of Clarice Lispector, Água Viva (The Stream of Life), observing attentively the narrative procedures employed by the author to create a frontier text. The expressiveness of this text tries to amplify the boundaries of language. The peculiarity of the textual and thematic structures creates in the act of reading a space in which a dialogue with the reader is better propitiated. Thus, questions concerning the interaction between this reader and the text were observed in accordance to the reading suggestions constructed by the selected literary work in order to propitiate routes of creation of senses.